(untitled) (Journal of the College of Basic Education, 2025)
This research aims to identify the reality of the use of modern teaching strategies by primary school teachers in the First Rusafa Education Directorate, in light of the rapid cognitive and technological transformations that education is witnessing, which have imposed radical changes on the role of the teacher and the teaching method. The descriptive analytical approach was used, and the number of research sample members was (100) male and female teachers, who were randomly selected. The researcher adopted a tool represented by a scale of modern teaching strategies, and after verifying its validity and reliability, it was applied in the field. The research results showed that male and female teachers possess a high level of knowledge and application of modern teaching strategies, as the arithmetic mean of the sample reached (52.97), which is higher than the theoretical average of (39), indicating a high level of interaction with contemporary educational trends. The results also showed no statistically significant differences between males and females in their level of use of modern teaching strategies, which reflects equal opportunities in training and professional qualification between the sexes. In light of the findings, the study reached a set of conclusions, most notably: the importance of continuous professional development, the effectiveness of modern teaching strategies in improving the learning environment, and the necessity of supporting educational policies that focus on efficiency rather than demographic factors. The study also presented a number of recommendations, most notably: enhancing practical training for teachers, providing appropriate educational tools and resources, and proposing future research that explores deeper aspects of this field.